(untitled) (The Pakistan Development Review, 1984)
The specific requirements of the performance evaluation system for public enterprises emanate from the peculiar characteristics of those institutions. The concept of public enterprise implicitly assumes the existence of two dimensions - the enterprise dimension and the public dimension. The enterprise dimension involves the setting up of a recognizable organization engaged in the production of goods and services, marketed at a price, and whose transactions are formulated through a system of commercial accounts such as balance sheets and profit-and-loss accounts_ The public dimension, on the other hand, involves public ownership, public management, and control, and assumes the existence of public purposes and the fulfillment of public interest [9. p. 39].